Studi Kasus Penggunaan Akun Instagram @life.at.prospect dalam Meningkatkan Internal Branding dan Employee Engagement - Hana Dhia Khoirunnisa Rachman; Nora Nailul Amal (Jurnal Komunikasi Massa, 2026)
This study examines the role of the Instagram account @life.at.prospect as an internal communication medium at Prospect Institute in strengthening internal branding and enhancing employee engagement. The account functions not only as a documentation platform but also as an informal communication channel that displays workplace dynamics, shared values, and a humanistic organizational culture. Through this platform, employees can access information, recall work experiences, and build closer social relationships with colleagues and the organization. This research employed a qualitative descriptive method with a case study approach (Yin, 2018). The informants were selected using a purposive sampling technique, considering that not all individuals within the Prospect Institute are directly involved with the @life.at.prospect account. Data were collected through in-depth interviews with eight informants—seven employees and one account manager—complemented by observation and content documentation. The data were analyzed using the interactive analysis model of Miles and Huberman (1984), including data collection, reduction, presentation, and conclusion drawing. The findings reveal that @life.at.prospect serves three main functions: as a documentation medium, an informal communication channel, and a platform for strengthening social relationships. These functions support the internal branding process by representing the organization’s authentic and collaborative values while increasing employee engagement through emotional, cognitive, and behavioral involvement.